Water quality. Determination of the acute lethal toxicity of substancesto a freshwater fish [Brachydanio rerio Hamilton-Buchanan (Teleostei, Cyprinidae)]. Flow-through method Part 3, (15th January 1998) - British Standards Institution,
No abstract available